Integration of Multi-Source Datasets for Assessing Ground Swelling/Shrinking Risk in Cyprus: The Case Studies of Pyrgos–Parekklisia and Moni - Argyriou, Athanasios; Prodromou, Maria; Theocharides, Christos; Fotiou, Kyriaki; Alatza, Stavroula; Loupasakis, Constantinos; Pittaki, Zampella; Kontoes, Charalampos; Hadjimitsis, Diofantos G.; Tzouvaras, Marios (My University, 2024)
The determination of swelling/shrinking phenomena, from natural and anthropogenic activity, is examined in this study through the synergy of various remote sensing methodologies. For the period of 2016–2022, a time-series InSAR analysis of Sentinel-1 satellite images, with a Coherent Change Detection procedure, was conducted to calculate the Normalized Coherence Difference. These were combined with Sentinel-2 multispectral data by exploiting the Normalized Difference Vegetation Index to create multi-temporal image composites. In addition, ALOS-Palsar DEMderivatives highlighted the geomorphological characteristics, which, in conjunction with the satellite imagery outcomes and other auxiliary spatial datasets, were embedded within a Multi Criteria Decision Analysis (MCDA) model. The synergy of the remote sensing and GIS techniques’ applicability within the MCDA model highlighted the zones undergoing seasonal swelling/shrinking processes in Pyrgos–Parekklisia and Moni regions in Cyprus. The accuracy assessment of the produced final MCDA outcome provided an overall accuracy of 72.4%, with the Kappa statistic,being 0.66, indicating substantial agreement of the MCDA outcome with the results from a Persistent Scatterer Interferometry analysis and ground-truth observations.Thus, this study offers decision makers a powerful procedure to monitor longer- and shorter-term swelling/shrinking phenomena.
Keywords: data fusion; optical; SAR; geohazards observatory; multi-criteria decision analysis